Crossing and stranding at edges: On intermediate stranding and phase theory. Issue 1 (28th February 2020) - Davis, Colin
Abstract : This paper investigates the distribution of stranding in intermediate positions under A′-movement, which I show obeys a cross-linguistically robust word order generalization: leftward movement of a phrase α can only intermediately strand an element β if β can be ordered rightward of α before stranding occurs. I argue that this generalization emerges naturally from the Cyclic Linearization theory of spell-out, and its interaction with independently supported constraints on movement in syntax. I go on to consider some reasons why a particular position may or may not be a viable location for stranded material.